Pharmacokinetics and preliminary safety data of a single oral dose of bosentan, a dual endothelin receptor antagonist, in cats. Issue 2 (24th October 2013) - Puza, N.; Papich, M. G.; Reinero, C.; Chang, C.‐H.; Yu, D.‐H.; Sharp, C.; DeClue, A.
<x xml:space="preserve">Abstract</x> The objective of this study was to evaluate the pharmacokinetic properties and adverse effect profile of single‐dose oral bosentan, a dual endothelin receptor antagonist, in healthy cats. Pharmacokinetic parameters were determined following a single mean ± SD oral dose of 3.2 ± 0.6 mg/kg of bosentan in 6 adult cats. Blood was collected for quantification of bosentan via high‐performance liquid chromatography with ultraviolet detection. Blood and urine were evaluated for CBC, plasma biochemical profile, and urinalysis, and repeat physical examinations were performed to evaluate for adverse effects. The mean terminal half‐life of bosentan was 20.4 ± 17.2 h. The mean peak plasma concentration was 0.49 ± 0.24 g/mL, and the mean time to maximum plasma concentration was 6.8 ± 8.6 h. The area under the curve was 5.14 ± 3.81 h·μg/mL. Oral bosentan tablets were absorbed in cats, and no clinically important adverse events were noted. Further evaluation of repeat dosing, investigation into the in vivo efficacy of decreasing endothelin‐1 concentrations in cats, as well as safety in conjunction with other medications is warranted.